V Techno-economic comparison between direct seeding and transplanting method in rice cultivation: a case study / Mohamad Hanif Nur Hidayat M. Zuki - M. Zuki, Mohamad Hanif Nur Hidayat (Faculty of Plantation and Agrotechnology, 2017)
The investigation was conducted to evaluate technical aspect of machine performance and economic feasibility between direct seeding and transplanting method in rice cultivation. This study used two type of paddy cultivation machine which is Kubota rice transplanter used for transplanting method and knapsack mounted motorized blower used for direct seeding method to operate this study in Paya Keladi, Seberang Perai, Pulau Pinang paddy field during June until November 2016. Both planting method had three unit plots of sized 100 m x 100 m each with two treatments and three replications. The operational performance from the result showed the field efficiency of the direct seeding method and transplanting method were 70.00 % and 63.58 %, respectively. Percent missing seedlings in transplanting method were 5.56 % while the direct seeding method was observed no missing seedlings. The planting efficiency of direct seeding method and transplanting method were 94.44 % and 100 %, respectively. Rice cultivated with transplanting method resulted in higher average yield of 11.20 tons/ha than direct seeding method resulted average yield of 9.10 tons/ha. The total production costs were RM 3770 per ha and RM 4420 per ha for direct seeding and transplanting methods, respectively. The net return for direct seeding method and transplanting method were RM 5785 and RM 7340, respectively. The benefit cost ratio (BCR) was 2.66 and 2.53 for transplanting method and direct seeding method, respectively. For economic planting of rice, the Kubota rice transplanter should have above 10 ha/yr of area coverage. The result showed that the transplanting method is more economic over the direct seeding method.